Application of Vision Technology and Artificial Intelligence in Smart Farming (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
Artificial intelligence (AI) and computer vision (CV) are increasingly applied in smart agriculture, offering significant potential to enhance farming efficiency, reduce manual labor, and lower production costs. In livestock farming, CV and AI enable behavior monitoring to improve animal health and welfare. In crop production, they support phenotype extraction, plant organ detection, and pest management. This Special Issue (Volume 2) presents original research and reviews on topics such as agricultural sensor optimization, livestock behavior recognition, AI-based automation, agricultural robotics, and big data analytics in farming.